2020
DOI: 10.1177/0095327x20934885
|View full text |Cite
|
Sign up to set email alerts
|

Military Service, Combat Experience, and Civic Participation

Abstract: Military service is a highly social—and potentially socializing—experience. However, the long-term social effect of military service is a little-studied topic, and some have dismissed any direct impact of service on civic participation. Using data from a large, national survey, our estimates show, in contrast, that the likelihood and intensity of group participation is higher among veterans than other men and that combat veterans have the highest level of participation. Mettler argued that education funded thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Civic engagement was limited to voting and community service. Specific aspects of veteran status have been shown to be important considerations as well, such as combat veteran or not (Ellison, 1992; Wilson & Ruger, 2008), draftee versus volunteer (Leal, 1999), and time period served (Teigen, 2006). These features were not present in the study data set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Civic engagement was limited to voting and community service. Specific aspects of veteran status have been shown to be important considerations as well, such as combat veteran or not (Ellison, 1992; Wilson & Ruger, 2008), draftee versus volunteer (Leal, 1999), and time period served (Teigen, 2006). These features were not present in the study data set.…”
Section: Discussionmentioning
confidence: 99%
“…There are several directions for future research examining civic engagement among veterans. Studies might further investigate civic engagement of veterans in varied populations, especially, those which past studies have shown to be associated with civic involvement—combat veterans (Wilson & Ruger, 2008), racial/ethnic groups (Ellison, 1992; Leal, 1999), different time periods (World War II, Korean War, the draft and volunteer Vietnam and post-Vietnam Era, etc. ; Teigen, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As former service members who are back in the civilian world, veterans represent the citizen–soldier tradition. As such, they have attracted the attention of social scientists who are interested in civil–military relations and the health of democracy (Cohen 1985; Feaver and Gelpi 2004; Feaver and Kohn 2001; Gelpi and Feaver 2002; Huntington 1957; Janowitz 1964; Snyder 1999) and the role of institutions such as the military in shaping political and civic engagement (Jennings and Markus 1977; Leal and Teigen 2018; Nesbit and Reingold 2011; Teigen 2006; Wilson and Ruger 2021). The study of soldiers and veterans is also intertwined with the establishment of quantitative social science.…”
Section: The Military and Social Sciencesmentioning
confidence: 99%
“…The literature on military service, politics, and public opinion remain surprisingly limited (Wilson and Ruger 2021). Researchers in this domain have long recognized that military service, and especially combat experiences, are often life‐changing events, turning points that can have a range of long‐term consequences as veterans return to civilian life (Elder 1986; Laufer 1988).…”
Section: The Military and Social Sciencesmentioning
confidence: 99%